In Vitro Bioaccessibility and Health Risk of Heavy Metals from PM2.5/PM10 in Arid Areas—Hotan City, China - Bowen Liu; Yuanyu Zhang; Dilinuer Talifu; Xiang Ding; Xinming Wang; Abulikemu Abulizi; Qilong Zhao; Xiaohui Zhang; Runqi Zhang (Atmosphere, 2023)
The impact of heavy metals in particulates plays an assignable role in human health—especially in the northwest region of China, which is affected by severe dust storms—and the bioaccessibility and health risks of heavy metals in particulate matter have not yet been quantified and evaluated. This study used Gamble’s solution and PBET (physiologically based extraction test) experiments to simulate the human respiratory and digestive systems, and analyzed the concentrations and bioaccessibility of Pb, Mn, Ni, Cd and As in PM2.5 and PM10 samples in the urban area of Hotan City during summer (July) and winter (January). The result shows that Mn and Pb are the most abundant elements in five metals. The bioaccessibility of Mn in gastric fluid was the highest in both summer (PM2.5: 64.1%, PM10: 52.0%) and winter (PM2.5: 88.0%, PM10: 85.1%). Meanwhile, in the respiratory system, the highest bioaccessibility of PM2.5 and PM10 in summer was Ni (53.3%), and Pb (47.9%), respectively. Although the concentration of Cd is low in winter, its bioaccessibility in lung fluid was the highest (PM2.5: 74.7%, PM10: 62.3%). The USEPA standard model and Monte Carlo simulation results show that the heavy metals in PM2.5 and PM10 would give rise to non-carcinogenic risk for both adults and children through the respiratory system in summer but had little risk in winter. However, the metal may have non-carcinogenic risk to children through intake. In addition, there is a cancer risk to adults through the respiratory system in winter (PM2.5: CR = 1.80 × 10−6, PM10: CR = 2.82 × 10−6), while there is a carcinogenic risk through the digestive system regardless of season and age.